PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MAN 1 MEDAN - Ananda Putri Khairunnisa (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to analyze the effect of the Numbered Heads Together (NHT) cooperative learning model on the mathematical communication skills of tenth-grade students at MAN 1 Medan. This study uses a quantitative approach with a quasi-experimental design of the nonequivalent control group design. The research subjects consisted of an experimental group of 36 students and a control group of 34 students. The data collection instrument was a mathematical communication ability test through a pretest and posttest. Data were analyzed using an independent sample t-test after fulfilling the normality and homogeneity tests. The results showed that the average posttest score of the experimental group was 84.88, higher than the control group of 80.47. The t-test results showed a significance value of 0.017